2007
DOI: 10.1590/s1415-47572007000100015
|View full text |Cite
|
Sign up to set email alerts
|

Generation mean analysis for quantitative traits in sesame (Sesamum indicum L.) crosses

Abstract: To study the nature and magnitude of gene effects for yield and its components in sesame (Sesamum indicum L.) we carried out generation mean analysis using the following four crosses of different sesame cultivars: VS 9510 x Co1; NIC 7907 x TMV 3; Cianno 13/10x VRI 1; and Si 1115/1 x TMV 3. The P 1 , P 2 , F 1 , F 2 , BC 1 and BC 2 of these generations were studied for seven quantitative traits. The analysis showed the presence of additive, dominance and epistatic gene interactions. The additive dominance model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Similarly, a significant negative additive × dominance gene effect for P‐incorporation efficiency was observed in the E × IF cross, indicating duplicate epistasis between additive‐ and dominance‐increasing alleles (Sharmila et al. ). At least two of the five gene effects were as significant for both PUE and P‐incorporation efficiency for the other crosses, except for E × ME, in which none of the gene effects were significant for PUE.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Similarly, a significant negative additive × dominance gene effect for P‐incorporation efficiency was observed in the E × IF cross, indicating duplicate epistasis between additive‐ and dominance‐increasing alleles (Sharmila et al. ). At least two of the five gene effects were as significant for both PUE and P‐incorporation efficiency for the other crosses, except for E × ME, in which none of the gene effects were significant for PUE.…”
Section: Discussionmentioning
confidence: 91%
“…The negative significant additive × dominance gene effect that was observed for root P in E × ME indicated that there was duplicate epistasis between additive‐ and dominance‐increasing alleles (Sharmila et al. ). Epistatic gene effects may be considered either complementary or duplicate depending on whether the additive × additive and dominance × dominance interactions are all significant and positive/negative or all significant with one negative and the other positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…parent 1 ( ), parent 2 ( ), first filial ( ), second generation ( ), first filial of the backcross with recurrent parent 1 ( ) and first filial of the backcross with recurrent parent 2 ( ). Generation mean analysis is a useful technique that provides the estimation of the average effects of the genes (additive, dominance and epistasis) involved in the expression of quantitative traits such as yield and yield components which benefits breeders in designing the most appropriate breeding approaches for developing a new varieties (Pooni & Treharne, 1994;Iqbal & Nadeem, 2003;Checa et al, 2006 andSharmila et al,2007). Genome scans for quantitative trait loci (QTL) have proved to be a successful strategy for identifying genetic effects and interactions (Carlborg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%